PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT BURHAN PURNAMA MURAKABI CRAFT KECAMATAN NANGGULAN KULONPROGO YOGYAKARTA - Sartika Yuliana; Sutiyem, Sutiyem; Fadhlan, Fadhlan; Ardian Samsudin (Media Bina Ilmiah, 2024)
Employee performance is the quality and quantity of work results achieved by an employee in carrying out their duties according to their responsibilities. Employee performance is the behavior or activities displayed by a person in relation to work tasks in a company, department or organization, carried out in accordance with the potential he has in order to produce something meaningful for the organization, wider society or himself. This research aims to determine the influence of work motivation and discipline on employee performance. The sample in this research is employees of PT. Burhan Purnama Murakabi Craft. totaling 100 people with purposive sampling technique. The data in this study were analyzed using multiple linear regression. The results of this research show that work motivation and discipline have a positive effect on employee performance. For this reason, managers need to carry out promotions targeting employees so that they can influence company performance